Immune-mediated attenuation of influenza illness after infection: opportunities and challenges - Manish M Patel, MD (Elsevier, 2021)
Summary: Sterilising immunity that blocks infection for life, and thus prevents illness after infection, is the ultimate goal for vaccines. Neither influenza infection nor vaccination provide sterilising immunity. Mutations during influenza viral genome replication result in the emergence of viruses that evade immunity and cause reinfections. Waning of immunity also results in reinfections to homologous influenza viruses. However, immunity might limit the severity of disease after infection or vaccination (ie, immunoattenuation). We provide a comprehensive examination of experimental and observational peer reviewed evidence since 1933, when the first influenza virus was isolated, on whether immunity blocks subsequent infection or attenuates illness. Although an abundance of experimental evidence supports immunoattenuation, clinical evidence is rudimentary and conflicting. To the extent that immunoattenuation occurs, understanding the varied pathways to illness, pathogenesis, clinical manifestations, and correlates of attenuation can improve the design and evaluation of influenza vaccines. By elucidating the mechanisms of immunoattenuation and phenotypes of illness, we clarify ambiguities and identify unmet needs that, if addressed with priority, could strategically improve the design of vaccines for the prevention of influenza.